Analisis Komoditas Unggulan Sub-Sektor Perkebunan Di Provinsi Sumatera Utara 2019-2023 - Nasution, Nanda Dwi Hartama; Salqaura, Siti Sabrina (Universitas Medan Area, 2025)
This This article aims to analyze the leading commodities in the plantation sub-sector and the base sector in North Sumatra Province, examine the structure and growth rate of commodity production within the plantation sub-sector, and assess the contribution of each leading commodity to the economy of North Sumatra Province. The study focuses on the analysis of structure, growth, and economic contribution. Data were collected from the Central Bureau of Statistics and analyzed quantitatively using the Location Quotient (LQ) formula, classical Shift Share Analysis (SSA), and Klassen Typology with the assistance of Microsoft Excel. The findings indicate that palm oil and coffee are base sectors (LQ 1). The plantation sector in North Sumatra is not influenced by national growth ( negative), with some commodities growing faster ( positive) while others grow more slowly ( negative). Only palm oil, cocoa, and tobacco possess a competitive advantage ( positive), while overall production performance is relatively good despite disparities ( varies). Based on the Klassen Typology, palm oil and coffee fall into Quadrant I (advanced and rapidly growing sector), rubber into Quadrant II (advanced but stagnant sector), and coconut, cocoa, sugarcane, tea, and tobacco into Quadrant III (potential for development).